PEMANFAATAN JERAMI PADI DALAM RANGKA BUDIDAYA PADI SAWAH BERBASIS ORGANIK DESA KARYASARI KECAMATAN RENGAS DENGKLOK KABUPATEN KARAWANG - Danapriatna, Nana; Kamilah, Ahya; -, Ismarani; Rahmanto, M Ikhwan; Najmulmunir, Nandang; Lutfiadi, Ridwan; Risti, Eka; Widia Putri, Tiu Ilia (DEVOSI, 2020)
One of the reasons for the decline in rice production in Indonesia is that most of the paddy fields are already degraded, which is characterized by, among other things, low organic matter content. straw produced in rice cultivation is 7 tonnes / ha. However, the components of rice straw are mainly cellulose, hemicellulose, lignin, and small amounts of protein which make the C / N value high. The methods used in this activity are in the form of counseling, demonstration plots / pilots of making rice straw compost, guidance and counseling, field applications or planting rice using compost, monitoring and field evaluation. The results of the community service that has been carried out in Karyasari Village, Rengas Dengklok District, Karawang Regency were carried out by 10 members and this research was carried out well and by monitoring to see how successful compost from agricultural waste was.